Variação lexical na Paraíba (PB) e no Rio Grande do Sul (RS): bobo, golada e loura. - Ferreira, Barbara Lilian Nascimento (2018)
Language is part of living in society, manifesting the result of interactivity between speakers and cultural, historical, and geographical aspects. Therefore, the present variational analysis was based on the speaking communities of Paraíba and Rio Grande do Sul, geographically distant regions and apparently distinct historical-social contexts, demonstrating, through the verification of the intra and /or extra linguistic factors that motivated the processes of variation in both, the approximation or the lexicon - dialectal distance between these states. Thus, this work investigated some cases of variation of the words swig, silly and blond, which are part of the standard brasilian portuguese language, with the purpose of demonstrating, through variational analysis, similarities and/or differences between the Portuguese spoken in Rio Grande do Sul and Paraíba. To perform this study, the Ethnographic Linguistic Atlas of the Southern Region of Brazil - ALERS (2011) was used as methodological basis. Besides that, this work also presents qualitative support, since it had as direct source of data (corpus) texts belonging to the journalistic domain and dictionaries. Concerning to the contribution of the present research to the academic environment, this work is justified by the fact that it considers relevant to understand that portuguese is constantly changing, so. the processes of linguistic variation are common. So, in this first stage of the analysis, it was possible to perceive that, along the investigations of the conjectures raised about the motivation and the criation of non-standard variants in Paraíba and Rio Grande do Sul, both states present some similarities among themselves, either in view of the historical context and the form in which the occurrences of variation occurred in each of them. However, linguistic observation of different geographical locations can demonstrate how each of these speaking communities relates to its inhabitants and to its language, revealing, thereby, cultural diversity and issues of influence in the characterization of local speech. Therefore, this analysis is not yet complete, because there are other variations that could not be analyzed in this first moment, which are relevant for the present study. In view of this, the enormous range of linguistic variety – such as phonetic, semantic or lexical variation - present in brazilian portuguese language, reflects the different elements that contributed for each place to presented unique characteristics that differentiated it from others, whether in the use of the language or by the own way of living of their societies. That said, the study of the systematic heterogeneity of language, as proposed by Variationist Sociolinguistics, besides allowing the understanding of linguistic variation, helps in the awareness and acceptance of social diversity. Considering that, Brazil is the mixture of different cultures and languages of people who were part, and still are, of the formation of their own people we can not attribute to the use of standard portuguese the status of the only correct language.